Three Narratives on the Changing Face of Global Commodities Market Structure - Diego Valiante (Credit and Capital Markets – Kredit und Kapital, 2015)
The commodity market structure has changed at an incredible pace in the last 20 years and is now subject to intense scrutiny by academics and policy-makers. Taking a long-term view of price formation, empirical findings show that international trade and finance, mostly driven by emerging markets demand, market liberalisations and technological developments in market infrastructure, have increased pro-cyclicality and interconnection among physical commodity markets. Price formation mechanisms are more sensitive to information flows. The interconnection with the financial system is strong and so the transmission of shocks from the financial system to commodity physical and futures markets. The rise of commodity-linked financial transactions was an important contribution to those developments. WTO commitments in international trade and expansionary monetary policies have promoted greater financial participation and so interconnection, which is also expressed by a greater pooling of commodity returns with returns of financial indexes (also defined here as the true 'financialisation" process). This paper represents an introduction to the functioning and structure of modern commodity markets. Three narratives emerge as key drivers of the modern global market structure: international trade, international finance and trading technology. – – Wandel der Marktstruktur globaler Rohstoffmärkte – Drei Erklärungsansätze Im vergangenen Jahrzehnt ist das Interesse an Rohstoffmärkten rasant angestiegen. Ein langfristiger Überblick über die Preisbildung zeigt einen Anstieg der Pro-Zyklizität und wechselseitiger Abhängigkeiten von physischen Rohstoffmärkten. Diese Entwicklungen sind zurückzuführen auf den internationalen Handel und Finanzsysteme, die vor allem durch die Nachfrage der Emerging Marktes und Marktliberalisierung getrieben werden, und den technologischen Fortschritt der Marktinfrastruktur. Der Preisbildungsmechanismus reagiert heute sensibler auf Informationsflüsse. Die gestiegenen, wechselseitigen Abhängigkeiten der Finanzsysteme erhöhen die Verbreitung von Schocks auf physische Märkte und Terminmärkte von Rohstoffen. Die Ziele der WTO für den internationalen Handel und die expansive Geldmarktpolitik der Zentralbanken führen zu einer höheren Beteiligung der Finanzmärkte, welche sich im Gleichlauf von Rohstoffrenditen und Renditen von Finanzindizes erkennen lässt (und als "financialisation" bezeichnet wird). Dieser Beitrag liefert eine Einführung in die Strukturen und Funktionsweisen von modernen Rohstoffmärkten. Dabei sind drei bedeutsame Erklärungsansätze für die neue Marktstruktur zu nennen: der internationaler Handel, das internationalen Finanzsystem und die Geldmarktpolitik, und zudem auch der technologische Fortschritt.
Keywords: Q02; F61; F62; E52; 330; Commodities market structure; International commodities finance; Financialisation; Price formation; Futures markets